Specificity of the Escherichia coli proline transport system. - Rowland, I (1975)
The presence of both the carbonyl portion of the carboxyl group at position 2 of the pyrrolidine ring and a secondary amine was essential for uptake of a compound by the proline permease of Escherichia coli. The permease possessed a high affinity for azetidine-2-carboxylic acid and for compounds with ring structures smaller than the pyrrolidine ring. Pipecolic acid, the higher homologue of proline, and its derivatives were not transported. Cis- and trans-3,4-methano-prolines, also six-membered ring structures, behaved anomolously in that they possessed a high affinity for the permease. The difference between the methano-prolines and other six-membered ring structures probably resides in the fact that the former exist in the "boat" configuration whereas the latter possess the "chair" configuration. In general, substituted prolines in the cis configuration displayed a higher affinity for the permease than did corresponding trans isomers, though the affinity for substituted prolines was influenced by the position, size, and polar or nonpolar nature of the substituent group. At O C many analogues with affinity for proline permease exchanged with intracellular proline, but some analogues, notably trans-3-methyl- and trans-4-methyl-L-prolines, though possessing high affinity for the permease, showed an almost complete inability to exchange with intracellular proline.